1989
DOI: 10.1152/ajpheart.1989.257.5.h1389
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in central venous pressure improve carotid baroreflex responses in conscious men

Abstract: To test the hypothesis that unloading cardiopulmonary receptors improves human carotid baroreceptor responsiveness we measured heart rate (HR) and mean radial artery blood pressure (BP) responses elicited by trains of neck pressure and neck suction from +40 to -65 Torr during graded lower body negative pressure (LBNP) at -5, -10, -15, -20, -35, and -50 Torr in eight healthy men. Gain of the carotid baroreflexes was determined from logistic modeling of the HR [expressed as R-R interval (RRI)] and BP responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(146 citation statements)
references
References 0 publications
9
135
2
Order By: Relevance
“…5 It has been suggested that this degree of plasma volume change could lead to increased baroreflex sensitivity. 9 In addition, estrogen and progesterone could indirectly alter baroreflex sensitivities by altering arterial distensibility, 10 thus changing the impact of pressure fluctuations on baroreceptor firing. Changes in baroreflex sensitivities may have occurred to maintain blood pressure in response to changes in other physiological systems during the course of the menstrual cycle or OC use.…”
Section: Discussionmentioning
confidence: 99%
“…5 It has been suggested that this degree of plasma volume change could lead to increased baroreflex sensitivity. 9 In addition, estrogen and progesterone could indirectly alter baroreflex sensitivities by altering arterial distensibility, 10 thus changing the impact of pressure fluctuations on baroreceptor firing. Changes in baroreflex sensitivities may have occurred to maintain blood pressure in response to changes in other physiological systems during the course of the menstrual cycle or OC use.…”
Section: Discussionmentioning
confidence: 99%
“…Also, some reports have suggested that the sensitivity of the arterial HR baroreceptor reflex may be increased with decreases in central venous pressure. 12 However, other studies have failed to demonstrate similar changes. 51314 Frequency domain analyses have been applied extensively over the last 10 years to the study of HR control.…”
Section: -3mentioning
confidence: 99%
“…The prolonged BP elevation is otherwise explained by a compensatory mechanism other than the arterial baroreflex, such as the cardiopulmonary baroreflex [6,7] or vestibulosympathetic reflex [8]. It is generally accepted that, in a prolonged stage ([2 min) of orthostasis, BP maintenance is supported by humoral factors [4,5].…”
Section: Other Compensatory Mechanismsmentioning
confidence: 99%
“…This blood shift then reduces the venous return, so that the cardiac output and blood pressure (BP) tend to decline. This BP reduction, however, is compensated partly by various reflex mechanisms including arterial baroreflex [4,5], cardiopulmonary reflex [6,7], vestibulosympathetic reflex [8], or venoarteriolar axon reflex [9], and thus BP is maintained during an upright posture. Improvement in orthostatic tolerance is achieved by improving orthostatic cardiovascular responses [10].…”
Section: Introductionmentioning
confidence: 99%